Data protection beyond data rights: Governing data production through collective intermediaries - Jamie Duncan (Internet Policy Review, 2023)
Considering calls for more collective approaches to governing data about people, this paper explores how such interventions have been envisioned and enacted by their proponents. I focus on four types of data intermediary: data trusts, decentralised autonomous organisations, data cooperatives and data unions. These collective governance mechanisms build on individualist data rights by embracing data as a form of collective value and redistributing benefits toward their members. While many privacy laws seek to balance competing commercial, public, and private interests in data, I argue these intermediaries work to align the social and economic value of aggregated data with the normative interests of individuals described in it. In detailing how these four mechanisms have been imagined and implemented, I find demand for collective data governance exists across many jurisdictions and a wide range of otherwise divergent ideological positions. This partial consensus provides an opening for lawmakers within and beyond the European Union to strengthen individual data rights through legal recognition for collective governance mechanisms to intervene in processes of data collection, management, and circulation.
Keywords: 300; Data rights; Decentralised Autonomous Organisations (DAOs); Data commons; Data governance; Data protection